Indonesian Linguistics and Culture Training: Building Bridges of Cross-Cultural Understanding from an Early Age - Mansyur, Firman Alamasyah; Haris, Abdul; Nengsih, Widya; Saleh, Rachman; Arsad, Arsad; Ridwan, Muhammad (Room of Civil Society Development, 2025)
This international Community Service activity was held at Lukmanulhakeem School, Yala, Thailand, with the aim of introducing the importance of understanding Indonesian linguistics and culture to teachers and students to strengthen cross-cultural understanding from an early age. The background of this program is based on the need for an understanding of cultural diversity from an early age as an effort to build tolerance and solidarity in the educational environment. The methods used are interactive training, cross-cultural discussions, and field visits. The material provided includes an introduction to the basic vocabulary of Indonesian language and culture, such as greetings and traditional foods and gotong royong traditions. The results of the activity showed that as many as 35 teachers succeeded in improving their understanding of the linguistic concepts of Indonesian culture. In conclusion, this program has succeeded in creating harmonious cross-cultural relationships and has a positive impact on improving the quality of education at Lukmanulhakeem School. For the continuation of this program, further assistance and the provision of technology-based learning media are needed to support the sustainability of implementation in partner schools.